PENGARUH PENERAPAN METODE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII SMP NEGERI 1 BAROMBONG - Jannah, Nurislahul; M, Nurhidaya; Firdaus, Andi Mulawakkan (Almeera Education, 2023)
The purpose of this study is to determine the application of the Think-Pair-Share method to the learning outcomes of class VIII students in the learning process of Islamic Religious Education at SMP Negeri 1 Barombong. This research uses a quantitative approach and using the type of experimental research. Then, the design used is